2014
DOI: 10.1145/2533686
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic Routing in Low Duty-Cycle Wireless Sensor Networks

Abstract: Opportunistic routing is widely known to have substantially better performance than unicast routing in wireless networks with lossy links. However, wireless sensor networks are usually duty cycled, that is, they frequently enter sleep states to ensure long network lifetime. This renders existing opportunistic routing schemes impractical, as they assume that nodes are always awake and can overhear other transmissions. In this article we introduce ORW, a practical opportunistic routing scheme for wireless sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 36 publications
0
70
0
Order By: Relevance
“…Many recent works [36,37,38] have observed that the packet errors are most likely to be bursty, i.e., the erroneous packets are often consecutive. As the key of network coding is to generate the non-linear combinations of the native packets, the consecutiveness poses new chance for lightweight error recovery code.…”
Section: Link Burstinessmentioning
confidence: 99%
“…Many recent works [36,37,38] have observed that the packet errors are most likely to be bursty, i.e., the erroneous packets are often consecutive. As the key of network coding is to generate the non-linear combinations of the native packets, the consecutiveness poses new chance for lightweight error recovery code.…”
Section: Link Burstinessmentioning
confidence: 99%
“…Ghadimi et al had proposed opportunistic routing in wireless sensor networks (ORW) routing protocol targeting applications with low duty cycles [11]. The protocol maintains a so called expected duty cycle (EDC) metric for all the neighboring nodes.…”
Section: Flat Protocolsmentioning
confidence: 99%
“…This line of research has been advanced in the European Framework Program, which has developed a wide range of routing algorithms that can naturally deal with mobility and exploit social relationships [31,30,20]. Service discovery [13] and opportunistic routing [17] for low duty-cycle lossy wireless sensor networks have been recently studied. A range of innovative approaches to security and metadata privacy has also been developed in this project [34,35,5].…”
Section: Related Workmentioning
confidence: 99%